Implementasi Program Pengembangan Kewirausahaan Muda Mandiri di STMIK Tasikmalaya - rahayu, Isyana; Sarmidi; Rohpandi, Dani; Mulyani, Evi Dewi Sri; Safitri, Mila Meiliani; SM, N. Nelis Febriani; Anwar, Dede Syahrul (Publikasi Pengabdian Masyarakat, 2022)
Many students are now also acting as entrepreneurs. However, there are also many students whose businesses do not run or stop because they do not have enough knowledge and mental abilities to be independent as entrepreneurs. This community service activity is based on empowering entrepreneurial students through entrepreneurship development and training programs in order to develop their businesses and increase income. The purpose of this activity is to increase skills and mental formation as independent young entrepreneurs. This study uses a qualitative method. Prospective young entrepreneurs are selected through several stages, namely the written selection stage 1, the written selection stage 2 and interviews. Of the 50 people who took part in the first stage of selection, 5 tenants were selected who were guided and trained to become independent young entrepreneurs. The assistance provided by the Lecturer team is to provide training and knowledge both online and offline to five selected young entrepreneurs in the STMIK Tasikmalaya student environment about business and how to manage it. The result of this research is that there is a change in the behavior of tenants to develop their business, starting from the motivation not to give up, the ability to solve problems, adding value and product quality through innovation to understanding the making of business proposals. Several things that can be concluded from this community service activity are that in general the problems that occur in the formation of independent young entrepreneurs for students are motivation, expertise and the ability to see opportunities.